2015
DOI: 10.1111/nep.12500
|View full text |Cite
|
Sign up to set email alerts
|

Dietary mobile apps and their effect on nutritional indicators in chronic renal disease: A systematic review

Abstract: The authors undertook a systematic review of studies that used mobile apps to modify the compliance with dietary restrictions of patients with chronic kidney disease. They found only two randomised controlled trials and three case reports and thus clinical benefit or harm could not be determined. ABSTRACT:Dietary apps for mobile technology are becoming increasingly available and can assist in recording food and fluid intake for nutrition assessment or monitoring. Patients with chronic renal disease, particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 16 publications
1
44
0
1
Order By: Relevance
“…However, having to undertake this dual recording of data both paper and online, could have also impacted on acceptability. Studies in populations with diabetes and renal disease support the suggestion that being able to input foods in real time via a phone app and adding other clinical data such as blood glucose levels can improve acceptability [13,14].…”
Section: Acceptabilitymentioning
confidence: 98%
See 3 more Smart Citations
“…However, having to undertake this dual recording of data both paper and online, could have also impacted on acceptability. Studies in populations with diabetes and renal disease support the suggestion that being able to input foods in real time via a phone app and adding other clinical data such as blood glucose levels can improve acceptability [13,14].…”
Section: Acceptabilitymentioning
confidence: 98%
“…The opportunity for continued use would have provided valuable insights into its usability and acceptability in participants with a health condition [14].…”
Section: Strengths and Limitations Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…A second study, related to the use of interactive web-based applications and videoconferencing for the telerehabilitation of people with multiple sclerosis [42], highlighted the lack of methodologically robust trials. A third article showed the potential clinical benefits of dietary interventions based on smartphone applications for chronic renal patients, although there is a need for additional robust trials [43]. Finally, a fourth article aimed to analyze the impact of smartphone applications targeting overweight or obese people, and concluded that when exclusively considering the use of mobile technologies (21 RCT), a significant reduction in weight was observed [27].…”
Section: Other Chronic Conditionsmentioning
confidence: 99%